The Novel Developed Lectin Nanoparticle Assay Displayed Promising Diagnostics to Pancreatic Cancer over the Conventional Assay - Hu, Xiaoyu (fi=Turun yliopisto|en=University of Turku|, 2018)
Pancreatic cancer (PCa) is one of the most aggressive cancers for both male and female. The survival rate is among the lowest (<5%) of any cancer because patients are already at an advanced stage when the disease is detectable. The early detection of this cancer provides the best opportunity of cure, which could not be achieved by the application of conventional carbohydrate antigen 19-9 (CA19-9) immunoassay with poor sensitivity and specificity. Against this background, cancer-related glycans on tumor markers have been reported to present at the early stage of cancer. Lectins have well-defined specificities to distinguish glycans compared to antibody; the binding affinity is low though. The binding affinity of lectins can be improved with avidity effect by coating on europium-doped nanoparticles that report signal in time-resolved fluorescence. Therefore, a novel CA19-9 assay with potentially improved performance of diagnostics can be developed by using lectins nanoparticles as tracer and CA19-9 antibodies as the capture. In this study, twenty-seven lectin nanoparticles, combined with five CA19-9 capture antibodies, were used to develop the new CA19-9 assay. Lectin-nanoparticles DC-SIGN indicated clear discrimination to CA19-9 with various concentrations in pooled healthy plasma matrix when combining with capture Bio-C241 and Bio-C192. The necessary optimizations were performed. Finally, EDTA-plasma samples from 10 PCa patients, 27 patients having a benign condition and 16 healthy volunteers were used to test the clinical utility of the lectin-nanoparticles assays. The FujireBio CA19-9 immunoassay was used as a control. DC-SIGN-Bio-C241/-Bio-C192 assay suggested a more convincing separation of PCa from healthy controls. The p-value of lectin assays was 0.0001 between PCa and healthy controls compared to 0.041 for the control. The fold difference of median concentrations was 5.9 from DC-SIGN-Bio-C241 assay and 3.9 from the control. Besides, the two lectins assays were strongly correlated with Pearson coefficient of 0.969. The improved separation between cancer and non-cancer individuals was achieved by the novel CA19-9 lectin nanoparticles assay.